(3cJGH aj GdWH dYed GdLQGMjfs - (3Nda Hf YHGS GdRgQGhqj GdCfOdSj, CHh GdbGSe,J (B427 (3g` s
(3ChdgG (B:s
(3bGd hGVY gPG GdcJGH deG GcedJ dce jG Hfi gPG GdcJGH GdPi gh LRA ef Yde GdWH GdHGH GdChd ai Gdci HGdfGQ s
(3BNQgG (B:s
(3hgj GdJi JXgQ ai XgQ GdbOe fMh GdNfUQ hGdHfUQ ef GdCYUGH hCQSd ef GdOe GdbOQ GdPi JQjO ced GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs